Minutiae point exraction for skeleton-based fingerprint image - Azril Nizam, Muhamad (2008)
A reliable personal identification is necessary due to the growing importance of information technology and the necessity of protection and access restriction. The key task is to identify the owner of the security system. A biometric security system verifies user identity by comparing the behavioral or physiological trait of the owner. Fingerprints are the oldest and most widely used form of biometric identification because of their high acceptability, immutability and individuality. Local characteristic called minutiae points represent fingerprints where the most prominent points are end point and bifurcation point. This project is a software design of minutiae point extraction for skeleton-based fingerprint image. There are four main components in the software design which are image pre-processing, minutiae extraction, post-processing and the graphical user interface (GUI). In the image pre-processing, image enhancement were executed which include loading an input image, binarize the image and thinning the image. In the minutiae extraction stage, end points and bifurcation points were located. The post-processing stage execute the removal of the false minutiae out of the fingerprint image and lastly, the graphical user interface (GUI) will access the image repository and display the output image at each processing stage hence, as the interface between the user and the software design.